Strategi Internasionalisasi Topeng Malangan oleh Padepokan Asmorobangun dalam International Mask Festival (IMF) Tahun 2023 - Rahmah Hidayatus Sholichah; Nur Luthfi Hidayatullah (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This research describes the internationalization strategy of Topeng Malangan applied by Padepokan Asmorobangun in the context of its participation in the International Mask Festival (IMF) in 2023. The main problem of this research focuses on how the traditional art of Topeng Malangan can adapt and be accepted in the international arena without losing its authentic values, with the argument that the right adaptation strategy can maintain the essence of local culture while attracting global audiences. Using a qualitative approach with a case study method, the results show that Padepokan Asmorobangun applies several adaptive strategies in internationalization, including: simplification of the duration of the performance from 9-10 hours to 10 minutes without losing the authentic essence, reduction in the use of verbal language, emphasis on characterization patterns through intensified movements and expressions, and selection of the story “Sayembara Adu Jago” which has universal values. Despite facing significant challenges in terms of funding and limited preparation time, participation in the International Mask Festival (IMF) 2023 has had a positive impact in the form of expanding international cooperation networks and increasing Padepokan Asmorobangun's reputation in the global arena. This research concludes that international festivals can be a strategic platform for cultural diplomacy and the internationalization of traditional arts, with adaptability and innovation being key success factors in introducing local cultural heritage to the global stage without losing the basic elements of Topeng Malangan.